Managing dry skin in patients with comorbidities or with advanced age: unmet needs and roles for products containing potential emollient-plus ingredients - Matthias Augustin; Enzo Berardesca; Ulrike Blume-Peytavi; Peter Elsner; Davide Scafa; Leonard Christopher Schmeel; Ehrhardt Proksch (Journal of Dermatological Treatment)
In dry skin (DS), skin-barrier function is easily disturbed and moisturizing factors in the stratum corneum are reduced. Despite being a common condition, DS is often overlooked in patients with advanced age or comorbid diseases. In September 2022, specialists in dermatology and skin care met to discuss unmet needs and management of patients with DS with existing medical conditions or DS induced by ongoing pharmacological treatments. There was consensus about the need to improve the current understanding and management of DS in patients with comorbidities, including type 2 diabetes, chronic kidney disease, radiodermatitis, and photodamaged skin. Clinical guidance related to optimal treatment of DS in patients with advanced age or comorbid diseases is needed. Dexpanthenol-containing emollients have been shown to provide rapid relief from the symptoms and clinical signs of skin inflammation and are well-tolerated and effective in terms of moisturizing and soothing DS and maintaining skin-barrier function. Thus, dexpanthenol-containing emollients may play an important role in future management of DS. Further research is needed to elucidate the efficacy of dexpanthenol across the spectrum of DS, irrespective of comorbidity status or age.